Updated Genome Assembly of Bighead Carp (Hypophthalmichthys nobilis) and Its Differences Between Male and Female on Genomic, Transcriptomic, and Methylation Level - Fu, Beide; Zhou, Ying; Liu, Haiyang; Yu, Xiaomu; Tong, Jingou (Frontiers in Genetics, 2021)
Cyprinidae is one of the largest family in freshwater fishes, and it is most intensively cultured fish taxon of the world. However, studies about sex determination in this large family is still rear, and one of the reasons is lack of high quality and complete genome. Here, we used nanopore to sequence the genome of a male bighead carp, obtaining contig N50 = 24.25 Mb, which is one of the best assemblies in Cyprinidae. Five males and five females were re-sequenced, and a male-specific region on LG19 was confirmed. We find this region holds many male-specific markers in other Cyprinidae fishes, such as grass carp and silver carp. Transcriptome analyses of hypothalamus and pituitary tissues showed that several sex-specific differentially expressed genes were associated with steroid biosynthesis. The UCH64E gene, located in the male-specific region on LG19, showed higher expression levels in male than female tissues of bighead carp. The methyl-RAD of hypothalamus tissues between males and females indicated that the sexual methylation differences are significant in bighead carp. We also compared the methylation sites recognized using methyl-RAD and nanopore raw reads and found that approximately 73% of the methylation sites identified using methyl-RAD were within nanopore CpG sites.